Pembuktian Tindak Perkosaan Berperspektif Korban Dalam Putusan Hakim - Laili Anisah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
This study aims to analyze the judges' perceptions regarding the sexual history of the victim whether or not it has an influence on the punishment of the perpetrators or not, because rape victims need more affirmative and gender-fair evidence to obtain substantive justice. This research is a normative study using a statute and comparative law approach, with the aim of minimizing the disparity of court decisions in the same case. The results of the study found that one of the decisions of the High Court in Indonesia in its decision did not use evidence that incriminated the defendants. This study also found that the evidence used was only evidence that lightened the defendants. The victim's experience and psychological condition are not included and are used as a consideration in the verdict.